Searching for a Definition of Refractory Irritable Bowel Syndrome: a Systematic Review and Meta-analysis - Peng, Wen-Yan; Ye, Kun; Qin, Di; Tang, Tai-Chun; Chen, Min; Zheng, Hui (Journal of gastrointestinal and liver diseases : JGLD, 2021)
Background and Aims: The pathological mechanism of irritable bowel syndrome (IBS) is unclarified, which commonly leads to unresponsiveness to conventional treatments. The diagnostic criteria for refractory IBS are not clearly defined. We performed a systematic review to summarize the key points of the definition of refractory IBS in different studies. We also conducted a meta-analysis to explore whether the diverse definitions for refractory IBS affect the therapeutic effect of gut-directed hypnotherapy (GDH). Methods: We searched OVID Medline, Embase and Cochrane (until September 2020) for randomized controlled trials (RCTs) recruiting patients with refractory IBS. We evaluated the definition of refractory IBS through the following aspects: duration of symptoms, unresponsive to dietary intervention, lifestyle modification, pharmacology, psychology, severity assessment and adequate explanation. The effect of the different definitions for refractory IBS on the therapeutic effect of gut-directed hypnotherapy (GDH) was checked by a meta-analysis. Results: Twenty-one RCTs were finally included. Six (28.6%) out of 21 RCTs recruited patients with symptoms lasting for over 12 months; 8 (38.1%) RCTs reported a prior use of dietary intervention; 1 (4.8%) RCT reported the use of lifestyle modification; 11 (52.4%) RCTs recruited patients who were unresponsive to pharmacology; 2 (9.5%) RCTs recruited patients with no response to psychological therapy ; 5 (23.8%) RCTs had symptoms severity assessment; and 8 (38.1%) RCTs recruited patients who were informed adequately. Despite being tested in trials with heterogeneous definition of refractory IBS, GDH had similar effectiveness when compared with supportive treatment [standardized mean difference (SMD)=-0.69, 95%CI: -0.93 to -0.44)] or waiting-list control (SMD=-0.54, 95%CI: -0.98 to -0.10). Conclusions: Varied definitions in refractory IBS were common phenomena in clinical studies. Resistance to symptom severity assessment and psychological treatments should be more explicitly defined. Gut-directed hypnotherapy was efficacious for refractory IBS and was not affected by the diversity in the definition of refractory IBS among RCTs.